Predictors and benefits of lipid-lowering therapy initiation after an atherosclerotic cardiovascular event: a retrospective cohort study - Casula, Manuela; Scotti, Stefano; Galimberti, Federica; Bruno, Giacomo Matteo; Colombo, Giorgio Lorenzo; Alieva, Asiiat; Xie, Sining; Catapano, Alberico Luigi; Olmastroni, Elena (Frontiers in Pharmacology, 2025)
BackgroundGuidelines recommend lipid-lowering therapy (LLT) after an atherosclerotic cardiovascular disease (ASCVD) event. This study investigated real-world LLT initiation rate and its effect on total mortality in the Lombardy region.MethodsIndividuals aged ≥40 with an ASCVD event between January and September 2022 were identified from Lombardy’s administrative data. The prevalence of LLT initiation within 3 months was estimated, and factors influencing treatment initiation were evaluated using multivariate logistic regression (odds ratios [OR] and 95% confidence intervals [95% CI]). One-year post-event mortality was analyzed.ResultsAmong 16,025 patients 41.14% did not receive a LLT after an ASCVD event. Treatment initiation was more likely in subjects hospitalized for a cardiovascular event (OR 2.22, 95%CI 2.07–2.38, vs. cerebrovascular event), in patients aged 51–60 years (OR 1.30, 95%CI 1.16–1.46), and in patients previously treated with antidiabetic (OR 1.42, 95%CI 1.25–1.62), antihypertensive (OR 1.96, 95%CI 1.80–2.13), and thyroid hormone replacement medications (OR 1.34, 95%CI 1.10–1.63). Conversely, older age (71–80 years: OR 0.79, 95%CI 0.71–0.87; >80 years: OR 0.47, 95%CI 0.42–0.52), female sex (OR 0.73, 95%CI 0.68–0.79), previous exposure to antithrombotic medications (OR 0.65, 95%CI 0.59–0.72), and polypharmacy (OR 0.90, 95%CI 0.81–0.99 for 5-9 medications, OR 0.61, 95%CI 0.52–0.72 for ≥10 medications) reduced the likelihood of treatment. Mortality at 1 year was 3.07% in treated versus 11.66% in untreated patients (p-value <0.001).ConclusionThis study underscores a suboptimal LLT initiation rate in post-ASCVD patients. Initiating LLT is associated with significantly reduced 1-year total mortality, highlighting the need to optimize secondary prevention strategies.